Characteristics and prognostic factors of Parkinson's disease patients with abnormal postures subjected to subthalamic nucleus deep brain stimulation. (December 2018) - Okazaki, Mihoko; Sasaki, Tatsuya; Yasuhara, Takao; Kameda, Masahiro; Agari, Takashi; Kin, Ittetsu; Kuwahara, Ken; Morimoto, Jun; Kin, Kyohei; Umakoshi, Michiari; Tomita, Yousuke; Borlongan, Cesario V.; et al.
Abstract: Objective: In Parkinson's disease (PD), abnormal postures are often accompanied, which interfere with rehabilitation and subsequent functional recovery. This study investigated the relationship between clinical characteristics and improvement in abnormal postures of PD patients who received subthalamic nucleus deep brain stimulation (STN-DBS). Methods: Seventy-four PD patients were included in this study. Clinical data were analyzed using the patients' functional status at pre- and post-STN-DBS, including anteflexion vs. non-anteflexion, scoliosis vs. non-scoliosis, improved anteflexion vs. non-improved anteflexion, and improved scoliosis vs. non-improved scoliosis. Results: In patients with anteflexion, UPDRS III motor score at off medication was worse than that of patients with non-anteflexion. Patients with scoliosis presented with more comorbid spinal deformity and longer disease duration than those without scoliosis. Cobb angle of patients with asymmetrical psoas major and erector spinal muscles was more than that of patients without the asymmetry. Patients with improved anteflexion after STN-DBS had thicker abdominal oblique muscle and transverse abdominal muscle than those of patients without improved anteflexion. Patients with improved scoliosis were significantly younger at PD onset than those without improvement. Conclusions: There were only a few prognostic factors recognized in patients with improved postures. The thick abdominal muscle for anteflexion and younger PD onset for scoliosis were significant factors for improvement by STN-DBS. Rehabilitation designed to maintain muscle for correct postures may contribute to the amelioration of abnormal postures by STN-DBS, although multicenter trials are needed. Highlights: PD patients with anteflexion displayed worse motor score. PD patients with improved anteflexion after STN-DBS exhibited thick abdominal muscle. PD patients with scoliosis showed comorbid spinal deformity and longer disease duration. PD patients with asymmetrical paraspinal muscle had scoliosis. PD patients with improved scoliosis after STN-DBS had a younger PD onset.